2020
DOI: 10.3390/plants9060716
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic and Antimicrobial Activities of Teucrium polium and Thymus decussatus Essential Oils Extracted Using Hydrodistillation and Microwave-Assisted Techniques

Abstract: Essential oils (EOs) have been described as promising eco-friendly secondary products of aromatic plants with several biological activities. The present study aimed to characterize the chemical composition and explore phytotoxic and antimicrobial activities of Teucrium polium and Thymus decussatus EOs extracted using hydrodistillation (HD) and microwave-assisted extraction (MAE) methods. Twenty-seven and twenty-eight compounds were identified from HD and MAE extracted EOs of T. polium, respectively. The oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 54 publications
(79 reference statements)
3
13
1
Order By: Relevance
“…These compounds may act individually or in synergy as phytotoxic agents (allelochemicals). Compared to other reported EOs, the A. ochroleuca EO is more phytotoxic against lettuce (plant model) than the EO of Teucrium polium [ 50 ], Eucalyptus grandis and E. citriodora [ 51 ], Acacia cyanophylla [ 52 ], and Eremanthus erythropappus [ 53 ]. The most abundant compound, trans -chrysanthenyl acetate, has been reported as the main compound of other plants’ EO, with phytotoxic activity, such as Artemisia herba-alba [ 28 ] and Chrysanthemum coronarium [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…These compounds may act individually or in synergy as phytotoxic agents (allelochemicals). Compared to other reported EOs, the A. ochroleuca EO is more phytotoxic against lettuce (plant model) than the EO of Teucrium polium [ 50 ], Eucalyptus grandis and E. citriodora [ 51 ], Acacia cyanophylla [ 52 ], and Eremanthus erythropappus [ 53 ]. The most abundant compound, trans -chrysanthenyl acetate, has been reported as the main compound of other plants’ EO, with phytotoxic activity, such as Artemisia herba-alba [ 28 ] and Chrysanthemum coronarium [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The dried aerial parts (250 g) of investigated Centaurea species were extracted for 3 h over a Clevenger-type apparatus using our previous protocol [ 53 ]. The EO samples kept were stored in sealed air-tight glass vials at 4 °C for analyses.…”
Section: Methodsmentioning
confidence: 99%
“…A microwave apparatus working at 2450 MHz and 1600 W maximum power (CEM Corporation, Matthews, NC, USA) was used to examine the plant species (250 g) under study using our previously reported protocol [ 53 ]. Extraction parameters: power, time and temperature were 800 W, 60 min and 100 °C respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, there is an increasing trend by researchers, scientists, and policymakers to integrate natural, eco‐friendly, and safer compounds such as EOs. The EOs were reported as a green eco‐friendly natural product that used as antimicrobial agents [7–13] . Also, the EOs were integrated as safe and powerful antioxidant compounds used in pharmaceutical and industrial applications as well as food preservation [2,10,14–22] …”
Section: Introductionmentioning
confidence: 99%